Sustainability Accounting and the Future of ESG Reporting: Investor Insights - Lestari, Putri Ayu; Gangodawilage, Damith (Yayasan Sinergi Kawula Muda, 2025)
This study explores investor perceptions of Environmental, Social, and Governance (ESG) reporting and its role in sustainable investment decision-making in Indonesia. Using a qualitative case study approach, data were gathered through in-depth interviews with institutional investors, financial analysts, and corporate executives. Thematic analysis revealed key factors influencing investor trust, including transparency, standardization, and third-party audits. The findings show that transparent and consistent ESG reports, especially those aligned with international standards like the Global Reporting Initiative (GRI) and Sustainability Accounting Standards Board (SASB), enhance investor confidence by improving comparability and reducing greenwashing risks. Third-party audits further strengthen the credibility of ESG disclosures. Despite these benefits, several challenges remain, such as regulatory inconsistencies, limited data availability, and the subjectivity of sustainability metrics. This research contributes to the understanding of ESG reporting’s impact on investment decisions and highlights the need for standardized frameworks and independent verification to build trust. Policymakers and corporations are encouraged to adopt uniform ESG standards and audit practices. Future studies should explore the effects of mandatory ESG disclosures and the role of technology in improving ESG reporting’s accuracy and transparency.